THE INFLUENCE OF EASE OF USE, FREE SHIPPING, AND CUSTOMER REVIEWS ON PURCHASE DECISIONS IN E-COMMERCE (A CASE STUDY ON STUDENTS OF THE ENTREPRENEURSHIP STUDY PROGRAM AT FEB UNM) - Nabil Hamdini Sani; Marhawati; Andika Isma; Muhammad Jufri; Asmayanti (JIEKA: Jurnal Integrasi Ekonomi, Keuangan, dan Akuntansi, 2025)
This study aims to determine whether the variables of Convenience, Free Shipping, and Customer Reviews have a simultaneous or partial effect on Purchase Decisions in E-Commerce among Entrepreneurship Program Students at FEB UNM. This research is a quantitative study with the independent variables of Convenience (X1), Free Shipping (X2), and Customer Review (X3), while the dependent variable is Purchase Decision on E-Commerce (Y). The population in this study consists of active students of the Entrepreneurship Study Program at FEB UNM from the 2021-2023 cohort, with a sample of 50 student respondents who have previously transacted on e-commerce using a non-probability sampling technique with the accidental sampling method. The data analysis used classical assumption tests with normality test, multicollinearity test, and heteroscedasticity test; as well as hypothesis tests with multiple linear regression, simultaneous test, partial test, and coefficient of determination test. Based on the data processing results through SPSS, the partial test results show that only the customer review variable has a partial influence on purchasing decisions in e-commerce, while the convenience and free shipping variables do not have a partial influence. Therefore, the first and second hypotheses in this study are rejected, and the third hypothesis is accepted. Meanwhile, the regression constant value is positive and the F-calculated value is greater than the F-table value, so the three variables simultaneously influence the purchasing decision on e-commerce with a coefficient of determination value of 0.354, and the fourth hypothesis in this study is accepted.